Sustainable development and climate change in the Caribbean - Terrelonge, Sophia C. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Assesses the impact of climate change on sustainable development in the Caribbean region. Analyzes case studies of selected regional economies, focusing on the social and economic impacts of climate change on the creation of resilient productive capacities.